Emotions in classroom language learning: What can we learn from achievement emotion research?. (November 2019) - Shao, Kaiqi; Pekrun, Reinhard; Nicholson, Laura J.
Abstract: Research on emotions and second language (L2) learning has proceeded for four decades, and L2 scholars have made important contributions in this overshadowed research area. However, advances in the field have failed to match the more general research on emotion and learning in psychology and education that has proven beneficial for understanding a broad range of emotions experienced in educational settings and has direct implications for classroom teaching. Specifically, the control-value theory (CVT) of achievement emotion, which addresses the origins and functions of diverse emotions in education, has gained strong momentum and emerged as a useful theoretical framework, although it is largely unknown and unused by L2 researchers. The present article aims to introduce the concept of achievement emotions into the L2 context and bridge the gaps between these two fields of emotion research. We first review research on emotions in second language acquisition (SLA) and identify crucial areas for improvement. Then, we discuss theory, measurement, and empirical studies related to the construct of achievement emotions. In conclusion, we call for an integration of research on achievement emotions with the field of emotions and instructed SLA and highlight the potential benefits of such an endeavor.